Intermediation Efficiency and Bank Profitability: Evidence from Foreign Exchange Private Banks - Mawarni, Aulia; Mardiyani (Ilomata International Journal of Tax and Accounting, 2026)
The Banking sector holds a crucial role in safeguarding financial system stability while fostering economic growth through its intermediation function. However, banking profitability in Indonesia has fluctuated due to intense competition for funds, slower credit expansion, and rising operational cost pressures. This study analyzes the effects of Third Party Funds (TPF) and asset growth on bank profitability, proxied by ROA, and examines whether NIM mediates these relationships in private foreign exchange commercial banks. This study contributes by focusing on IDX-listed private foreign exchange banks during 2022-2024 and testing NIM as a mediatior between TPF, Asset Growth, and ROA using a unified path model.  Empirical evidence focusing on this bank segment and recent observation period remains limited in the Indonesian banking profitability literature. This research adopts a quantitative approach, using secondary financial statement data for the 2022-2024 period, and selects samples purposively from 17 banks. Data were analyzed using path analysis with LISREL 8.8. The findings indicate that TPF and asset growth significantly affect ROA. TPF also significantly influences NIM, while asset growth does not. Moreover, NIM significantly affects ROA but fails to mediate the effects of TPF and asset growth on profitability. These results imply that profitability improvement is driven mainly through direct fund utilization and productive asset expansion rather than interest margin mechanisms.